Adapting the informed push model to the last mile of the contraceptive supply chain in South Kivu in the Democratic Republic of Congo. - Katherine H LaNasa; Michel Yalaza; Felix Hitayezu; Frank Roijmans (Public Library of Science (PLoS), 2024)
In the Democratic Republic of Congo (DRC), contraceptive security is one of the largest barriers to improving access to family planning. This article presents findings from a pilot study that adapted an informed push distribution model to the last mile of the contraceptive supply chain, between the health zone pharmacy and health facilities, in the eastern region of DRC. The intervention consisted of three changes in the supply chain: organization of more efficient transportation routes, in-depth involvement of the community in supply chain management and bundling of contraceptives with other essential medications for efficient delivery. The intervention was implemented from October 2017 to October 2018 in the Katana health zone of the South Kivu province. Although there was not a statistically significant difference in availability of contraceptives during the pilot study period, there were sharp declines in the mean length of stockouts at health facilities and the monthly transportation costs of delivering contraceptives. Overall, the pilot study demonstrated it is feasible to adapt the IPM to a new location with complex geographical, political and socioeconomical influences. Future studies will be required to evaluate whether the adapted informed push model is more effective than the existing pull supply chain system for contraceptives in the DRC.